Analisis Teknologi Informasi Dalam Pengambilan Data Manajemen Bisnis - Anis Fazannah Mahiroh; Eli Ermawati Tambak; Muhammad Rijai Hasibuan; Ajmi Sahid Siahaan; Nurbaiti . (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
The benefits of information technology in business data acquisition will be examined in-depth, including the enhancement of an organization's ability to make data-driven decisions. Furthermore, obstacles and challenges associated with the implementation of information technology in business management will be discussed, such as data security issues and costs. Through a comprehensive literature review and conceptual analysis, this article will elucidate how information technology has transformed the paradigm of data acquisition in business management. By providing a robust conceptual framework, this article will aid business stakeholders and researchers in understanding the pivotal role of information technology in data acquisition and business management, paving the way for improved operational effectiveness and better decision-making in the future.